Residential Proximity to Major Roadways and Prevalent Hypertension Among Older Women and Men: Results From the Chinese Longitudinal Healthy Longevity Survey - Yao, Yao; Cao, Kaixi; Zhang, Kehan; Zhu, Tinglong; Yue, Dahai; Zhang, Hao; Zhang, Jim; Jin, Xurui; Zeng, Yi (Frontiers in Cardiovascular Medicine, 2020)
Background and Objectives: Prior studies suggested that residential proximity to major roadways was associated with increased risks of cardiovascular diseases in developed countries, for which one explanation is that road proximity could heighten the risks of hypertension. However, the association of residential distance to major roadways with hypertension is still unclear in low and middle-income countries (LMICs) with levels of air pollution and socioeconomic development distinctively different from developed countries. Methods: We derived data from the 8th wave of Chinese Longitudinal Healthy Longevity Survey (CLHLS), a nationwide prospective cohort. The present study included 12,881 individuals aged over 65 years (mean age: 85.2 ± 11.7) with 55.8% of them being female. We ascertained the residential proximity to major roadways based on self-reports and hypertension was defined as systolic blood pressure ≥140 mm Hg or diastolic blood pressure ≥90 mm Hg. We then used logistic regression to examine the association between residential distance to major roadways and hypertension. Results: The odds ratios (ORs) of hypertension for participants living 50-100 meters, 101-200 meters and ≥200 meters from major roads were 1.17 (95% CI: 1.02, 1.33), 1.21 (95% CI: 1.05, 1.41), and 1.22 (95% CI: 1.10, 1.34), respectively, compared to those living within 50 m. Significant effects of modifications from socioeconomic status and accessibility to healthcare resources were observed (Ps for interaction<0.05). Compared to living within 50 m from a major roadway, the odds ratios of hypertension for living ≥50 m were higher in manual/agricultural workers, low-education groups, participants without household ventilation, and participants lacking in health education and healthcare resources. We observed considerable variations across geographic regions with the association in question attenuating in Eastern China but remaining significant in other regions. Conclusion: Residential proximity to major roadways was associated with lower odds of hypertension among older adults in China. The utility of residential proximity to major roadways as a marker of increased risks of hypertension and cardiovascular diseases may need to be revisited in LMICs.